Analisis Kinerja Keuangan Sebelum Dan Sesudah Penerapan Pola Pengelolaan Keuangan Badan Layanan Umum Di Universitas Negeri Padang - Muhammad Syahromi; Charoline Cheisviyanny (Universitas Negeri Padang, 2020)
This study aims to determine how thefinancial performance before and after the application of thefinancial management patterns of public service agency (PK BLU) at Universitas Negeri Padang.This study usedquestionnairesand interviews to collect data. The population was academic community (students, lecturers, and university staffs) of Universitas Negeri Padang. We use convenience sampling method to select sample. The data was analyzed withseveral measurement methods: financial statements analysis and public satisfaction index.The results showed that the performance of Universitas Negeri Padangwas getting better after the application of PK BLU, even though the ratio was still not stable. While the level of community satisfaction after the implementation of PK BLU reached good satisfaction index 70.02. Based on theinterviews with lecturers and university staffs, theystated that PK BLU doesnot have a directly impact on students’ interest in the teaching and learning process but has an impact of the number of infrastructures to support the teaching and learning process. It concluded that there were manypositive changes after the implementation of PK BLU such as flexibility in financial management, financial planning, budget use, and financial reporting